Student Evaluation of Teaching - McCready, Douglas J. (Canadian Journal of Higher Education, 1981)
The analysis of factors which influence student valuations of teaching is the subject of this paper. An empirical test, using the evaluations carried out in the School of Business and Economics at Wilfrid Laurier University shows that the grades granted by instructors do not relate significantly to the evaluations of that instructor by students. Factors which do relate to higher evaluations include: early morning classes, small classes, optional subjects, and senior classes. From a survey of how faculty react to the evaluations, it appears that most faculty do not find the evaluations useful in making improvements in their own teaching.